MICRONEU: A NEW NOVEL DYNAMIC NON-LIVING MICROSURGERY MODEL - Ozad, Ulvan (LIFE: International Journal of Health and Life-Sciences, 2016)
Microsurgery is a niche area of surgery in which training and manual dexterity are essential. With limitations in live animal use for training, numerous non-living and synthetic microsurgical models have been designed, tested and used in microsurgery training. The main problem in non-living animal models is absence of the dynamic circulation. MicroNEU has been designed to attempt to add a dynamic circulation to non-living animal models in order to overcome the greatest disadvantage of these models in an economical way.